Any guidance would be greatly appreciated

For i)

A ∪ (A' ∩ B) = A ∪ B

LHS= A ∪ (A' ∩ B)

= (A ∪ A') ∩ (A ∪ B)

= U ∩ (A ∪ B)

= A ∪ B

= RHS

Is that right?

For the second question I am confused how to work with that many complements?

A ∪ (( B' ∩ A) ∩ A'= U

How do I tackle this?

Thankyou

#### Top Answer

The best way to approach your question... View the full answer

- Please ask if you have any doubt
- math_phys_EE_helper
- Apr 02, 2018 at 7:13am

#### Sign up to view the full answer

#### Other Answers

Here is a detailed explanation... View the full answer

i) your proof is... View the full answer

for second part I am using complement sign istead bar. you should use de-morgan law ( B c ∩ ... View the full answer